Literature Review: Factors Affecting the Intention of Vasectomy in Married Men - Rini Pratiwi; Silvia Kristanti Tri Febriana; Oski Illiandri; Musafaah Musafaah; Meitria Syahadatina Noor (GLOBAL HEALTH SCIENCE GROUP, 2026)
Male participation in vasectomy remains low globally and in Indonesia, despite evidence suggesting that psychological and social factors contribute to intention formation. The persistent imbalance in contraceptive responsibility suggests that intention, not just access, plays a central role. Objective to synthesize empirical evidence regarding the determinants influencing married men's intention to undergo vasectomy, focusing on attitudes, partner support, community norms, and perceived incentives within the framework of the Theory of Planned Behavior. The research design used was a literature review. The review was conducted by searching, reading, and analyzing relevant scientific articles to understand the factors influencing married men's intention to undergo vasectomy. This study used the SPIDER approach consisting of sample, phenomenon of interest, design, evaluation, and type of study. Articles were searched through Google Scholar, PubMed, and Scopus databases using access filters between 2021 and 2025. Keywords used in the search were